2014
DOI: 10.1186/s12883-014-0166-3
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation over primary motor vs non-motor cortical targets; effects on experimental hyperalgesia in healthy subjects

Abstract: BackgroundHigh frequency repetitive transcranial magnetic stimulation (rTMS) targetted to different cortical regions (primary motor/sensory, prefrontal) are known to alter somatosensory responses. The mechanism(s) for these effects are unclear. We compared the analgesic effects of rTMS at different cortical sites on hyperalgesia induced using topical capsaicin cream.MethodsFourteen healthy subjects had capsaicin cream applied to a 16 cm2 area of the medial aspect of the right wrist (60 min) on 4 separate occas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 42 publications
4
47
1
1
Order By: Relevance
“…However, pain processing is highly distributed throughout the brain. A small study recently demonstrated a trend towards reduction of acute pain after rTMS application to the occipital cortex, 104 and this approach was considered unacceptable in a recent systematic review. 58 Blinding TMS administrators is even more difficult and currently best addressed by coils that can be remotely programmed to deliver sham or true pulses, for instance, by opposing current flow within the loops to cancel their magnetic fields 46 or with a commercially available sham-capable system such as a MagVenture MagPro.…”
Section: Transcranial Magnetic Stimulation: Principles and Applicamentioning
confidence: 99%
“…However, pain processing is highly distributed throughout the brain. A small study recently demonstrated a trend towards reduction of acute pain after rTMS application to the occipital cortex, 104 and this approach was considered unacceptable in a recent systematic review. 58 Blinding TMS administrators is even more difficult and currently best addressed by coils that can be remotely programmed to deliver sham or true pulses, for instance, by opposing current flow within the loops to cancel their magnetic fields 46 or with a commercially available sham-capable system such as a MagVenture MagPro.…”
Section: Transcranial Magnetic Stimulation: Principles and Applicamentioning
confidence: 99%
“…Multiple types of experimental pain have been used to study the effects of NIBS on nociceptive signaling in healthy human subjects [74]. tDCS of M1 produces sustained analgesia in chronic migraine, fibromyalgia, and orofacial pain [38].…”
Section: Pain Modulation Using Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…Lack of a credible placebo coil hampers treatment blinding. We chose to use active stimulation over the occipital fissure for SHAM as it has been used in other studies with success and we believe to be preferable to coil rotation or tilt (2,40,68). To our knowledge, there have been no robust validation studies for the utility of "placebo" coils, although some studies appear to have used them successfully (42,69).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Experimental and clinical studies suggest that stimulation of primary motor cortex (M1) induces analgesia (1)(2)(3)(4)(5). Several controlled trials show that repetitive transcranial magnetic stimulation (rTMS) attenuates neuropathic pain, although the effect is modest and relatively short-lived (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%